Absence of Biological Mothers in Infancy in Children and Adolescents on Diagnosis of Mental Disorders at Ikeswar Outpatient Clinic, Prof. Dr. Soerojo Mental Hospital, Magelang - Edith Humris; Susi Rutmalem Bangun; Bayu Soenarsana Putra; Sak Liung; Kornelis Ibrawansyah (Scientia Psychiatrica, 2021)
Introduction. Globally, psychopathological problems in children and adolescents will become one of five problems that cause disability, morbidity, and even mortality in the next 20 years. The quality of a child's early attachment relationship is closely related to future brain and personality development. Attachment disorders are associated with the development of psychopathology in childhood and adulthood. This study aims to describe mental disorders in children and adolescents due to mothers who leave their children in infancy on Java, especially around Magelang. Methods. The type of this research is cross-sectional, namely descriptive research. The sample in this study were all patients and their parents/guardians who came for a consultation to the Ikeswar Polyclinic, Mental Hospital Prof. Dr.Soerojo Mental Hospital started on February 18, 2019. The examination uses the mental status determined and guided by PPDGJ III (Guidelines for Classifying the Diagnosis of Mental Disorders). Results. Most of the research respondents was male, both in children with excellent or poor attachment. As much as 26.1% in the group with suitable attachment. The age of most respondents is ten years old. The fourth axis diagnosis regarding psychosocial and environmental problems that most respondents experienced was primary support group (family) problems Conclusion. The attachment of the biological mother to the child at the age of fewer than two years is essential for the emotional mentality of the child at the age afterward and there is no visible picture of the difference in diagnosing mental disorders in children with suitable attachment and poor attachment.